A comparative study on LPWAN standards: Nb-IoT and LTE-M - Adamou Ismael Hamidou; Laguidi Ahmed; Mejdoub Youssef (ITM Web of Conferences, 2023)
Given the proliferation of connected objects as well as the rise of Low Power Wide Area Network (LPWAN) technologies designed to enable communication with low energy, the main ones being NB-IoT and LTE-M in our daily life. This is why in this article; our study will focus on the evaluation of the specificities of these two standards: NB-IoT and LTE-M